2001
DOI: 10.1007/978-94-015-9717-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to Adulthood in Europe: Conclusions and Discussion

Abstract: For most European countries the timing of first marriage and first parenthood are no longer the only and most appropriate indicators of the transition from youth to adulthood. This is so because both events were not only postponed, they also became increasingly disconnected from age and from each other. Moreover, among the female post-war cohorts there was a growing inter-dependence between the occupational and family career. These were good reasons to broaden the study of the transition from youth to adulthoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
12

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 12 publications
2
96
0
12
Order By: Relevance
“…Several authors have reported that age is an important correlate of parent-child proximity. In Germany and the United States, adult children typically leave the parental home between the end of their teenage years and the end of their twenties (Goldscheider & Goldscheider 1993, Corijn & Klijzing 2001. At this early stage of adulthood, parents are still an important source of instrumental, emotional, and financial support, suggesting that initial move-outs rarely bridge greater geographical distances.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Several authors have reported that age is an important correlate of parent-child proximity. In Germany and the United States, adult children typically leave the parental home between the end of their teenage years and the end of their twenties (Goldscheider & Goldscheider 1993, Corijn & Klijzing 2001. At this early stage of adulthood, parents are still an important source of instrumental, emotional, and financial support, suggesting that initial move-outs rarely bridge greater geographical distances.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…The transition to adulthood in many economically developed countries has become more protracted and de-standardized (Billari and Liefbroer 2010;Corijn and Klijzing 2001;Furlong and Cartmel 2007). The decline of traditional, predictable, trajectories of transitions to work and family life has been viewed as evidence of individualization, with young adults negotiating "elective biographies" that are increasingly unbounded by pre-existing social structures (Beck 1992;Giddens 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The decline of traditional, predictable, trajectories of transitions to work and family life has been viewed as evidence of individualization, with young adults negotiating "elective biographies" that are increasingly unbounded by pre-existing social structures (Beck 1992;Giddens 1991). Previous research has emphasized trends in the average age at leaving home and entry into partnership or parenthood, particularly postponement (Billari and Liefbroer 2010;Corijn and Klijzing 2001;Iacovou 2002). Important differences in the timing of leaving home according to individual and parental resources, family structure, region of residence, and state support have also been highlighted (Blaauboer and Mulder 2010;Buck and Scott 1993;de Jong Gierveld, Liefbroer, and Beekink 1991;Goldscheider 2000;Iacovou 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During the 1980s the age of leaving the parental home was increasing in many developed countries after a period of decline (Billiari et al 2001;Molgat 2002;Young 1987;Corijin & Klijzing 2001). A recent Australian study has found that leaving home still occurs during early adulthood and has not experienced the delay felt in other demographic or lifecourse events.…”
Section: Age Left Parental Homementioning
confidence: 99%